Impact of technology in temporomandibular joint reconstruction surgeries: A systematic review. Issue 6 (June 2021) - Kumar, Sumit; Khanna, Vikram; Singh, Balendra P.; Mehrotra, Divya; Patil, Ranjit K.
Summary: Objectives: The digital technologies, in recent years, have integrated with temporomandibular joint reconstruction surgeries (TRS). Therefore, a systematic study was conducted to assess the impact of digital technologies in TRS. Besides, a brief comparison between the CAD/CAM and 3D printing (3DP) technologies is presented. Materials & Methods: We searched in PubMed, ProQuest and Science direct using PRISMA guidelines. Population = Patients undergoing TRS, Intervention=CAD/CAM or 3DP, Comparison= conventional TRS (cTRS) vs technology integrated TRS (tiTRS), Outcome= Advantages/disadvantages of technology and Subjective/objective symptoms, Study design= Type of study. The quality of observational study was assessed using ROBINS-1 Assessment tool. Results: Out of 632 articles, 30 articles for CAD/CAM and 3DP were included in the study. A majority of TRS were done for ankylosis (new or re-entry), earlier failed surgery, osteoarthritis and neoplastic cases. The articles were divided into two groups. Group I: CAD/CAM( n  = 16), Group II: 3DP ( n  = 14). Discussion: tiTRS had definite advantages over cTRS with lesser surgery time, defined osteotomies, précised implant fitting and better final result outcome however, evidence for tiTRS in long-term follow-up is inconclusive. The cost, time, infrastructure and ethical/regulatory issues are the downsides of assisted surgeries. It was observed that 3DP technology is versatile and its adaptation in the fabrication of customized implants has outpaced CAD/CAM technology. However, literature data is feeble qualitatively and quantitatively. Conclusion: The TRS has leveraged the flexibility and precision of assisted surgeries. In future, tiTRS could successfully replace cTRS, provided that shortcomings should be dealt so that the technology can benefit the masses.